Comparison of Optical Properties of Laminate Veneers Made of Zolid FX and Katana UTML Zirconia and Lithium Disilicate Ceramics - Fariborz Vafaei; Alireza Izadi; Samaneh Abbasi; Maryam Farhadian; Zahra Bagheri (Tehran University of Medical Sciences, 2020)
Objectives: This study aimed to compare the optical properties of Zolid FX, Katana UTML, and lithium disilicate laminate veneers. Materials and Methods: In this in-vitro experimental study, the maxillary left lateral incisor of a phantom received a laminate veneer preparation. An impression was made, and a die was fabricated using dental stone. The die was scanned using a computer-aided design/computer-aided manufacturing scanner. Ten dies were fabricated from each of the A1, A2, and A3 shades of composite resin. Laminate veneers were fabricated using A1 shade of Katana UTML, Zolid FX, and IPS e.max CAD ceramics (n=10) and placed on composite abutments using bleach and white colors of trial insertion paste (TIP). The optical properties were measured at the incisal, middle, and cervical thirds using a spectrophotometer. Data were analyzed using three-way analysis of variance and Tukey's test. Results: The effect of laminate material on the L*, a*, and b* parameters was significant in all areas (P<0.001), except for the L* parameter in the middle and cervical thirds. All color parameters were affected by TIP color in all three regions in most samples (P<0.05). The effect of composite abutment shade was also significant in most cases (P<0.05). The effect of laminate material, abutment shade, and TIP color on the b* parameter was significant (P<0.001). The L* parameter was almost the same in the two zirconia and lithium disilicate ceramic groups. Conclusion: The composite abutment shade, TIP color, and laminate material should be carefully selected to achieve optimal aesthetics in laminate veneers.